Resposta do manjericão (Ocimum basilicum L.) cultivado em solos corrigidos com calcário e escória silicatada: Caracterí sticas agronômicas e produção de matéria seca - Deus, Angélica Cristina Fernandes [UNESP]; Santana,Graciele Sarante [UNESP]; Fernandes, Francisco Maximino [UNESP]; Sasaki, J. L S [UNESP] (My University, 2008)
Amongst the aromatic herbs, basil has great economic importance in Brazil. However, there is not enough information on the response of these plants to the soil acidity. For this reason, this experiment aims to evaluate some agronomical characteristics and dry matter production (stem and leaf) of a particular type of basil, regarding the corrective applications on two soils with lime and calcium silicate slag. The experiment was carried out under greenhouse conditions and the randomized blocks design with 20 treatments and 4 replications has been used. The height, branches number and dry matter mass from stem and leaves have been evaluated in two crop systems. In crop system 1, the soil type has influenced the dry matter production of stem and leaf, and the best production was on red latosol with medium texture. In both crop systems, 1 and 2, the plants were higher when growing on red latosol with clay texture, and it has also been observed that the plants' height and the branches number have not been influenced by the corrective doses. In fact, the branch number has not been influenced at all, not even by the soil type.
Response of basil (Ocimum basilicum L.) to limestone and silicate slag applied in soil: Agronomical characteristic and dry mass production
Keywords: Corrective applications; Latosol; Medicinal plants; Ocimum; calcium silicate; limestone; agronomy; basil; dry mass; greenhouse; nonhuman; plant height; plant leaf; plant stem; soil; Ocimum basilicum